IS IT NECESSARY TO REMOVE WISDOM TEETH - Gubayev Mukhitdin Sarimsokovich (European Science Publishing, 2024)
Wisdom teeth are the 8th tooth in a row, the third molar (there are 4 in total), usually erupt at the age of 17-25 years (sometimes later, less often earlier, sometimes they do not erupt — they remain retentive). Incompletely erupted teeth are called "semi-refined". Wisdom teeth are laid in humans in the prenatal period of development (in the womb), like others. Their absence is considered a variant of the norm in dentistry, not a pathology.